Autozygosity and Genetic Differentiation of Landrace and Large White Pigs as Revealed by the Genetic Analyses of Crossbreds - Gomez-Raya, Luis; Rauw, Wendy Mercedes; Dunkelberger, Jenelle R.; Dekkers, Jack C. M. (Frontiers in Genetics, 2019)
Genomic information from crossbreds is routinely generated for genomic evaluations. The objective of this study is to investigate autozygosity and genetic differentiation in Landrace by Large-White breeds by using the genotypic information of SNP arrays in 1,173 crossbreds. A maximum likelihood approach was developed to estimate the probability of autozygosity (FL). Regions of differentiation between breeds were investigated using FST and the difference in allele frequencies between the two parental breeds (Δ) at each Single Nucleotide Polymorphism (SNP) position. A maximum likelihood approach was proposed to estimate allele frequencies in the parental populations. The average length of Runs of Homozygosity (ROH) across the genome was 3.91Mb. The probability of autozygosity was not uniform along the crossbred genome, being higher at the centre for most chromosomes. The correlation between autozygosity and distance to the closest telomere was positive and significant in most chromosomes, which could be attributed to the higher recombination rate near telomeres. We also report a relatively high negative correlation between probability of recombination (from a published map) and probability of autozygosity. It supports that structural characteristics of the chromosomes related to recombination rate determine autozygosity at each chromosomal position of the pig genome. The average Δ across the genome was 0.17 (SD=0.16). After testing for differences in allele frequencies between the parental breeds, there were 4,184 SNPs with a Likelihood Ratio Test, LRT ≥ 32.02. The average FST across the genome was 0.038 (SD=0.059). There were 2,949 SNPs with FST > 0.125. The correlation between estimates of FL and estimates of FST across the genome was -0.10 (SE=0.006). Analysis of the gene content of the genomic regions with the 2000 SNPs with highest LRT for FL and high FST showed overrepresentation of genes with a regulatory function. Genes with biological functions associated with production, such as tissue development, anatomical structure, and animal organ development, were also overrepresented in regions with a high FST.